(3EMJQGa EOGQI GdTHcGJ HGSJNOGe GdNGOe (BMicrosoft windows server 2003 /s - (3YfGfj, YeQhs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3fXQI YGeI(B- (3EOGQI GdNhGOe(B- (3eQGbHI GdYedjGJ hGdNOeGJ hGdGMOGK(B- (3CJeJI GdELQGAGJ hGdSjGSGJ hGdegGe GdEOGQjI(B- (3GdJYGed eY NOeGJ GdJOYje hSWM GdecJH GdHYjO(B- (3GSJNOGe GdOdjd GdfTW(B- (3CSGS EOGQI GdOdjd GdfTW(B- (3eGgjI MSGHGJ GdeLehYI hMSGHGJ GdeSJNOejf(B- (3GfTGA MSGHGJ GdeSJNOejf hMSGHGJ GdeLehYGJ(B- (3EOGQI MSGHGJ GdeSJNOejf hGdeLehYGJ(B.s
Keywords: (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs; Microsoft windows server 2003